2015
DOI: 10.1590/0102-311x00099814
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of cause of death coding: an international comparison

Abstract: This study evaluates the agreement of nosologic coding of cardiovascular causes of death between a Chilean coder and one in the United States, in a stratified random sample of death certificates of persons aged ≥ 60, issued in 2008 in the Valparaíso and Metropolitan regions, Chile. All causes of death were converted to ICD-10 codes in parallel by both coders. Concordance was analyzed with inter-coder agreement and Cohen’s kappa coefficient by level of specification ICD-10 code for the underlying cause and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
1
13
0
5
Order By: Relevance
“…Haghighi et al (2014) recorded 62.6% male prevalence which is above that of this study. However, Antini et al (2015) and Nojilana et al (2009) recorded 59.2 and 51% female prevalence, respectively, which is antipodal to findings of the present study.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Haghighi et al (2014) recorded 62.6% male prevalence which is above that of this study. However, Antini et al (2015) and Nojilana et al (2009) recorded 59.2 and 51% female prevalence, respectively, which is antipodal to findings of the present study.…”
Section: Discussionsupporting
confidence: 69%
“…Studies conducted in South America (Antini et al, 2015), Asia (Haghighi et al, 2014) and Africa (Izegbu et al, 2006) have confirmed high incidence of inaccuracies in death certification. Contrarily, some measures have been put in place over the years to ensure accurate death certification in many countries such as USA, Scotland, Finland and Sweden (Lahti and *Corresponding author.…”
Section: Introductionmentioning
confidence: 97%
“…Pese a esto, las bases de datos ministeriales siguen siendo, a nivel internacional, la herramienta más comúnmente empleada para la estimación de la magnitud de las enfermedades, en particular aquellas basadas en diagnósticos de egreso. En el caso de la IC, las estadísticas de mortalidad y egresos hospitalarios, utilizadas habitualmente para determinar la carga de enfermedad, subestiman la prevalencia, puesto que no siempre se reconoce como una entidad nosológica independiente de otra enfermedad del sistema cardiovascular 26,27,[31][32][33][34] . Hay factores como la dificultad en el diagnóstico, la ausencia de marcadores específicos, la clasificación de la IC como mediador y no como causa de muerte, y la deficiente calidad de los registros hospitalarios que favorecen la subestimación de la IC como problema de salud 35 .…”
Section: La Principal Limitación De Nuestro Estudio Es Elunclassified
“…The quality and reliability of MCCD for use in mortality studies is a source of scrutiny and debate: studies in Australia, Chile, Estonia, Sri Lanka, Greece, the United Kingdom and the United States have noted common problems as being ill‐defined causes of death or modes of death, improper causal sequences and the mechanism rather than the cause of death being reported (Antini, Rajs, Munoz‐Quezada, Mondaca, & Heiss, ; Bell, Gaitatzis, Johnson, & Sander, ; Bugeja, Clapperton, Killian, Stephan, & Ozanne‐Smith, ; Cheng, Lu, & Kawachi, ; Katsakiori, Panagiotopoulou, Sakellaropoulos, Papazafiropoulou, & Kardara, ; Rahu, Palo, & Rahu, ; Rampatige, Gamage, Peiris, & Lopez, ).…”
Section: Introductionmentioning
confidence: 99%